Qatar : 2012 Article IV Consultation. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
Qatar's economy is driven by high oil and natural gas prices and production, and remains strong with robust nonhydrocarbon growth. Its government has now shifted its focus to economic diversification and growth in nonhydrocarbon sectors through targeted infrastructure investments. The Executive Directors of the International Monetary Fund (IMF) noted the positive regional spillover effects of Qatar's high growth, public spending, and increased financial assistance. The adoption of a three-year budget framework to help shield government spending from revenue volatility and enable better use of resources is welcomed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet